The Mitochondria-Targeting Agent MitoQ Improves Muscle Atrophy, Weakness and Oxidative Metabolism in C26 Tumor-Bearing Mice - Pin, Fabrizio; Huot, Joshua R.; Bonetto, Andrea (Frontiers in cell and developmental biology, 2022)
Cancer cachexia is a debilitating syndrome characterized by skeletal muscle wasting, weakness and fatigue. Several pathogenetic mechanisms can contribute to these muscle derangements. Mitochondrial alterations, altered metabolism and increased oxidative stress are known to promote muscle weakness and muscle catabolism. To the extent of improving cachexia, several drugs have been tested to stimulate mitochondrial function and normalize the redox balance. The aim of this study was to test the potential beneficial anti-cachectic effects of Mitoquinone Q (MitoQ), one of the most widely-used mitochondria-targeting antioxidant. Here we show that MitoQ administration (25 mg/kg in drinking water, daily) in vivo was able to improve body weight loss in Colon-26 (C26) bearers, without affecting tumor size. Consistently, the C26 hosts displayed ameliorated skeletal muscle and strength upon treatment with MitoQ. In line with improved skeletal muscle mass, the treatment with MitoQ was able to partially correct the expression of the E3 ubiquitin ligases Atrogin-1 and Murf1. Contrarily, the anabolic signaling was not improved by the treatment, as showed by unchanged AKT, mTOR and 4EBP1 phosphorylation. Assessment of gene expression showed altered levels of markers of mitochondrial biogenesis and homeostasis in the tumor hosts, although only Mitofusin-2 levels were significantly affected by the treatment. Interestingly, the levels of Pdk4 and CytB , genes involved in the regulation of mitochondrial function and metabolism, were also partially increased by MitoQ, in line with the modulation of hexokinase (HK), pyruvate dehydrogenase (PDH) and succinate dehydrogenase (SDH) enzymatic activities. The improvement of the oxidative metabolism was associated with reduced myosteatosis ( i.e. , intramuscular fat infiltration) in the C26 bearers receiving MitoQ, despite unchanged muscle LDL receptor expression, therefore suggesting that MitoQ could boost β-oxidation in the muscle tissue and promote a glycolytic-to-oxidative shift in muscle metabolism and fiber composition. Overall, our data identify MitoQ as an effective treatment to improve skeletal muscle mass and function in tumor hosts and further support studies aimed at testing the anti-cachectic properties of mitochondria-targeting antioxidants also in combination with routinely administered chemotherapy agents.